2023
DOI: 10.1021/acs.jpclett.3c00998
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Increased CO2 Capture Performance of Amino Acid Functionalized Nanoporous Materials from First-Principles and Grand Canonical Monte Carlo Simulations

Abstract: Nanoporous materials such as metal−organic frameworks (MOFs) and covalent−organic frameworks (COFs) have been identified as key candidates for environmental remediation through catalytic reduction and sequestration of pollutants. Given the prevalence of CO 2 as a target molecule for capture, MOFs and COFs have seen a long history of application in the field. More recently, functionalized nanoporous materials have been demonstrated to improve performance metrics associated with the capture of CO 2 . We employ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
3
7
0
Order By: Relevance
“…Lorentz–Berthelot combining rules define the nonbonded interactions between atoms of different types . As a large number of simulation studies have shown that the universal force field (UFF) can well predict the adsorption and diffusion of guests in various MOFs, the LJ potential parameters were taken from the UFF for functionalized MOFs. The atomic charges of MOFs were estimated by the extended charge equilibration (EQeq) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Lorentz–Berthelot combining rules define the nonbonded interactions between atoms of different types . As a large number of simulation studies have shown that the universal force field (UFF) can well predict the adsorption and diffusion of guests in various MOFs, the LJ potential parameters were taken from the UFF for functionalized MOFs. The atomic charges of MOFs were estimated by the extended charge equilibration (EQeq) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…They range from 2932.4 to 3105.4 cm À 1 , which agrees well with the experimentally assigned vibration bands for the CÀ H stretch of glycinate ligands in the produced MOF-808-Gly (approximately 2960 cm À 1 ), providing validation for utilizing the MOF cluster model in this study. [18] CO 2 Adsorption and Capture Mechanism First, the adsorption of CO 2 on MOF-808-Gly was studied. Two possible positions where CO 2 can be adsorbed on MOF-808-Gly were considered.…”
Section: Cluster Modelsmentioning
confidence: 99%
“…These adsorption positions have been previously identified as the two most stable locations for CO 2 adsorption by amino acid-functionalized MOF-808. [18] The optimized structures for CO 2 adsorption on all the MOF-808-Gly variants are shown in Figure S2 in the Supporting Information. In the first position, CO 2 mainly interacts with the site of the glycine amino group, whereas in the second position, CO 2 binds to both the H of the glycine amino group and the MOFs linkers via hydrogen bonds.…”
Section: Cluster Modelsmentioning
confidence: 99%
“…The authors found that the computational results were in agreement with experimental investigations under 10 bar and 298 K. At pressures higher than 10 bar, computational and experimental results were significantly different because of the unsuitable force field under high pressure conditions. Recently, Stanton et al also used the GCMC technique to predict the CO 2 adsorption of various MOF structures that were modified with amino groups [ 43 ]. This study could provide adequate information for further experiments in CO 2 storage areas.…”
Section: Reviewmentioning
confidence: 99%